BANYUWANGI CUSTOM RITUAL ETHNOBOTANY-BASED MODULE DEVELOPMENT ON BIODIVERSITY MATERIALS TO TRAIN PLANT LITERACY AND PROBLEM-SOLVING ABILITY - Nuris Fattahillah; Siti Sriyati; Amprasto Amprasto (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
The development of this teaching material aims to provide other alternatives in learning activities in the material chapter on biodiversity. The result of this teaching material is in the form of a biodiversity module based on the ethnobotany of Banyuwangi's traditional rituals with the aim of training plant literacy and students' problem-solving skills. The conventional rituals used in the module development are seblang Olehsari, seblang Bakungan, and petik laut Muncar. Module development uses the ADDIE method (Analyze, Design, Development, Implementation, and Evaluate) but module development only reaches the development stage. The modules made are tested for the feasibility of teaching materials and readability tests. The feasibility test of teaching materials consists of material coverage, material accuracy, material up-to-date, insight, appearance, and writing. The results of the eligibility validation of teaching materials showed a validity value of 88.70% with a very high category and showed that the module was very suitable for use in learning, while the results of the readability test using the cloze test contained 5 discourses consisting of 43 questions showing a readability level of 73% in the high category so that students easily understand the module developed in the readability aspect.